Child Safety Monitoring and Notification Gadget in Smart Town/City using IoT - S., Vasantha Kumar; S., Chandhini; S., Kowshika; K., Monisha Priya; A., Silambarasan; M., Vasanthi (Journal of Ubiquitous Computing and Communication Technologies, 2024)
This study suggests a brand-new child safety device for smart cities that uses the Internet-of-Things (IoT) to give parents real-time monitoring and alerts about the child. With the use of a variety of sensors, including a temperature sensor to monitor ambient conditions, a touch sensor to detect simple presses or contact on the device’s surface, a heartbeat sensor to measure fundamental health, and GPS for location tracking, this device is able to collect vital data about the child’s well-being. Parents can view their child’s data remotely. The microcontroller unit processes the data and sends it to a specified server. To notify parents of possible risks, such as exceeding a set temperature threshold, detecting a fall, or the child wandering beyond approved safe zones, a notification system is put in place. The device can also have a buzzer installed for instant local alerts in an emergency. Using the user-friendly Firebase software, parents can track their child’s whereabouts continuously with the device’s GPS module. This all-inclusive strategy improves child safety within the smart city infrastructure by giving parents peace of mind and enabling prompt action when needed. This device aligns with the expanding trend of smart city development, which uses technology to enhance the safety and well-being of its residents. Through its smooth integration with current IoT networks and infrastructure, this solution provides a useful and efficient way to protect kids in cities.